Peer Tutoring as a Collaborative Strategy to Strengthen EFL Secondary Students’ Reading Comprehension - herlina, Herlina; Astri Riance; Aliyah Miranti (Edu-Ling: Journal of English Education and Linguistics, 2025)
This study investigated the effectiveness of peer tutoring as a collaborative instructional approach to improve reading comprehension among EFL secondary school students. A pre-experimental design was employed over six sessions, consisting of four treatment meetings. The participants were thirty-six eleventh-grade students from a secondary school in Lubuklinggau who were enrolled in a reading comprehension course. Data were obtained through a reading comprehension test administered twice, namely as a pre-test prior to the intervention and a post-test following the treatments. The findings demonstrated an increase in the students’ mean score from 65.00 in the pre-test to 75.00 in the post-test. Moreover, the paired-samples t-test revealed a calculated t-value of 8.196, which exceeded the critical t-table value of 1.684. These results confirmed the acceptance of the alternative hypothesis (Ha). Thereby indicating that Peer Tutoring exerted a significant and positive effect on the reading comprehension achievement of EFL secondary students.